Exemplary Of Standing And Grounds On Judo - Aliyev Iskandar Bakhromovich; Ramazonov Khondamir Rauf o'gli (Genius Journals, 2023)
The aim of this study is to compare standing fight and fight in groundwork ratios of judo athletes by weight categories. Ratios of the scores by weight and sex categories confirm how to plan training design. The results of this investigation may help coaches and athletes to effectively plan their technical and tactical training
Keywords: judo; competitive activity; ratios of scores; standing fight